The enhancement of enzymatic hydrolysis of lignocellulosic substrates by the addition of accessory enzymes such as xylanase: is it an additive or synergistic effect? - Hu, Jinguang (BioMed Central, 2011)
BACKGROUND: We and other workers have shown that accessory enzymes, such as β-glucosidase, xylanase, and cellulase cofactors, such as GH61, can considerably enhance the hydrolysis effectiveness of cellulase cocktails when added to pretreated lignocellulosic substrates. It is generally acknowledged that, among the several factors that hamper our current ability to attain efficient lignocellulosic biomass conversion yields at low enzyme loadings, a major problem lies in our incomplete understanding of the cooperative action of the different enzymes acting on pretreated lignocellulosic substrates. RESULTS: The reported work assessed the interaction between cellulase and xylanase enzymes and their potential to improve the hydrolysis efficiency of various pretreated lignocellulosic substrates when added at low protein loadings. When xylanases were added to the minimum amount of cellulase enzymes required to achieve 70% cellulose hydrolysis of steam pretreated corn stover (SPCS), or used to partially replace the equivalent cellulase dose, both approaches resulted in enhanced enzymatic hydrolysis. However, the xylanase supplementation approach increased the total protein loading required to achieve significant improvements in hydrolysis (an additive effect), whereas the partial replacement of cellulases with xylanase resulted in similar improvements in hydrolysis without increasing enzyme loading (a synergistic effect). The enhancement resulting from xylanase-aided synergism was higher when enzymes were added simultaneously at the beginning of hydrolysis. This co-hydrolysis of the xylan also influenced the gross fiber characteristics (for example, fiber swelling) resulting in increased accessibility of the cellulose to the cellulase enzymes. These apparent increases in accessibility enhanced the steam pretreated corn stover digestibility, resulting in three times faster cellulose and xylan hydrolysis, a seven-fold decrease in cellulase loading and a significant increase in the hydrolysis performance of the optimized enzyme mixture. When a similar xylanase-aided enhancement strategy was assessed on other pretreated lignocellulosic substrates, equivalent increases in hydrolysis efficiency were also observed. CONCLUSIONS: It was apparent that the 'blocking effect' of xylan was one of the major mechanisms that limited the accessibility of the cellulase enzymes to the cellulose. However, the synergistic interaction of the xylanase and cellulase enzymes was also shown to significantly improve cellulose accessibility through increasing fiber swelling and fiber porosity and also plays a major role in enhancing enzyme accessibility.